Framing Effects on Online Security Behavior - Rodríguez-Priego, Nuria; van Bavel, René; Vila, José; Briggs, Pam (Frontiers in Psychology, 2020)
We conducted an incentivized lab experiment examining the effect of gain vs. loss-framed warning messages on online security behavior. We measured the probability of suffering a cyberattack during the experiment as the result of five specific security behaviors: choosing a safe connection, providing minimum information during the sign-up process, choosing a strong password, choosing a trusted vendor, and logging-out. A loss-framed message led to more secure behavior during the experiment. The experiment also measured the effect of trusting beliefs and cybersecurity knowledge. Trusting beliefs had a negative effect on security behavior, while cybersecurity knowledge had a positive effect.